(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Blunt chest trauma is a significant cause of morbidity and mortality, often leading to a range of cardiac complications detectable through electrocardiogram (ECG) abnormalities. Objectives: The primary objective of this research was to identify the early onset of myocardial damage in patients with acute blunt chest injuries using ECG. The secondary objective is being to compare the ECG changes between paediatric and adult trauma patients. Methodology: This cross-sectional study was conducted in the Emergency department (ED) and patients admitted with acute blunt chest trauma were included in the current study. A total of 281 patients were included based on the following inclusion criteria: patients of all ages with blunt chest trauma. Exclusion criteria included preexisting cardiac and neurological conditions, penetrating chest injuries, pregnant women and incomplete medical records. Demographic and clinical data were collected, and a standard 12-lead ECG was performed and analyzed for abnormalities. Statistical analysis was done using SPSS version 26, where chi square test was applied to identify factors that may be associated with ECG abnormalities and assess age-related differences in ECG findings. Results: ECG findings in patients with blunt chest trauma, recorded in 30.9% of the total sample. Sinus arrhythmia’s, particularly sinus tachycardia were the most common findings in both adults (6.2%) and pediatrics (8.1%). In adult’s sinus tachycardia was followed by ST segment changes and atrial fibrillation. In pediatrics, sinus tachycardia was accompanied by PVCs and supraventricluar tachycardia. Conclusion: Sinus arrhythmias were the most common findings in both group, followed by ST segment changes and atrial fibrillation in adults while in pediatrics, followed by PVCs and SVT.